Pengaruh Pengetahuan Perpajakan, Self Assesment System, Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak (Studi Kasus Pada Wajib Pajak Orang Pribadi Di Kpp Pratama Bojonagara) - Yogi Ardiansyah; Arry Irawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Tax is one of the largest and most important sources of state revenue that is used for the benefit of the community. However, in practice, the number of taxpayers who pay and report taxes has been often not in accordance with government targets, especially at the Bojonagara Tax Service Office (KPP) the compliance of individual taxpayers in paying and reporting taxes is still relatively low, especially from 2018-2020. Then this study aims to determine whether knowledge of taxation, self-assessment system, and tax sanctions can affect taxpayer compliance, especially individual taxpayers registered at KPP Bojonagara. This research was conducted in KPP Pratama Bojonagara Bandung, especially on individual non-employed taxpayers using a quantitative approach. In collecting the required data, the author uses a questionnaire as a research instrument. Then the sampling technique in this study using non-probability sampling, namely convenience sampling. The results of this study partially show that Tax Knowledge has a significant and negative effect on taxpayer compliance, Self Assessment System has a significant and positive effect on taxpayer compliance, Tax Sanctions have a significant and positive effect on taxpayer compliance. Simultaneously, Tax Knowledge, Self Assessment System, and tax sanctions have a significant effect on taxpayer compliance.